Blackhearts : ecology in outback Australia - Symanski, Richard (Yale University Press, 2000)
This fascinating book is a firsthand account of the adventures of an ornithological field team studying long-tailed finches in outback Australia. In 1991, Nancy Burley, a noted behavioral ecologist, and her husband, Richard Symanski, went to Australia with their one-year-old son and four American students hired as field assistants and babysitter. The social relationships and problems that developed among these individuals in confined and exotic settings and the scientific discoveries that did -- and did not -- take place form the heart of the book. Symanski begins by telling how he and his wife set up this elaborate field expedition -- including the hiring of what seemed to be qualified, compatible, and knowledgeable field assistants. He then describes the harsh realities of their circumstances in Australia: primitive living conditions on an outback cattle station; field sites and subjects for study that were not as expected; and students who were not prepared for the rigors of field life and who became unenthusiastic about the work for which they had been hired. And he tells how he and his wife strove to overcome all the different challenges with which they were confronted. The book provides insight into the demands of professor-student-based fieldwork, particularly when generational conflicts, differing expectations, and culture shock complicate the "business" of doing science